Cyclin E/CDK2 and feedback from soluble histone protein regulate the S phase burst of histone biosynthesis - Claire Armstrong; Victor J. Passanisi; Humza M. Ashraf; Sabrina L. Spencer (Cell Reports, 2023)
Summary: Faithful DNA replication requires that cells fine-tune their histone pool in coordination with cell-cycle progression. Replication-dependent histone biosynthesis is initiated at a low level upon cell-cycle commitment, followed by a burst at the G1/S transition, but it remains unclear how exactly the cell regulates this burst in histone biosynthesis as DNA replication begins. Here, we use single-cell time-lapse imaging to elucidate the mechanisms by which cells modulate histone production during different phases of the cell cycle. We find that CDK2-mediated phosphorylation of NPAT at the restriction point triggers histone transcription, which results in a burst of histone mRNA precisely at the G1/S phase boundary. Excess soluble histone protein further modulates histone abundance by promoting the degradation of histone mRNA for the duration of S phase. Thus, cells regulate their histone production in strict coordination with cell-cycle progression by two distinct mechanisms acting in concert.